Capacitive and Inductive Line Reactance for Network Reconfiguration - Aiman Suhailah Saifuddin; Karmila Kamil; Halimatun Hashim; Ruthraganapathy Radhakrishnan (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Solar PV may cause power congestion to occur in a transmission line when there is high solar irradiance that causing solar PV to generate more power flow than demanded power flow. Transmission line congestion that can be made worst by adding extra power generating farm such as centralized PV farm of renewable energy which helps to deliver customers with the demand or load required. The power generated coming from solar PV is depending on the weather and can definitely worsen the flow in transmission line due to the power captured. In this case, the high solar irradiance can affect the power generated from solar PV and will cause power congestion when power generated is higher than the load demanded. In this paper, the proposed method used to overcome the power congestion in a transmission line is by rerouting the excess power from the overloaded line to underloaded line by changing the line reactance of the line. An IEEE 30 bus test system is developed in PSS/E software as the test system. The output monitored is the line stability index of the affected line before and after rerouting process.